Translation and Dictionaries (Journal of Human Sciences, 2023)
In this research, the researcher, with God’s will and success, will study two terms: (translation) and (dictionaries) and everything related to both of them from the scientific side.This research includes two sections:(1) the first section (translation) which includes the definition of translation in the language, and in the terminology, types of translation, its conditions, and the most famous methods of translation, and the importance of translation, and is translation a science? Or art? Or a profession? Or a theory?(2) the second section (dictionaries) which includes the definition of the lexicon in the language, and in the terminology, and what is the real history to define the word lexicon historically? What are the aspects of agreement and disagreement among modern Arabic scholars between (lexicon) and (dictionary)?The second section also includes the divisions of linguistic dictionaries, and what are the three most famous divisions of them for modern Arabic scholars? And clarifying the relationship between translation and dictionaries, and talking about the role of translation towards dictionaries, and the role of dictionaries towards translation, then the conclusion of the research including the most important results reached by the researcher, mentioning references and comments at the end of the research, followed by mentioning sources and references.